The Role of Control Cards in Shaping Students' Citizenship in Schools - Ahmad Bakri; Dadang Sundawa; Iim Siti Masyitoh (JED (Jurnal Etika Demokrasi), 2023)
The rapid development of the times today is a challenge in building the character of students. The challenges faced by all nations related to the nature of citizenship have become national issues that require a comprehensive study to take strategic steps to overcome the problem. The application of control cards is one of the flagship programs owned by SMA Negeri Bernas Binsus Provinsi Riau, in building the character of its students. This study aims to explore and analyze the role of control cards in shaping the civic disposition of students at SMA Negeri Bernas Binsus Provinsi Riau. This research uses qualitative design with case study method. Data research techniques use observation, interviews and documentation. The results of this study show that, with the control card plays a role in forming civic disposition including (1) discipline, obeying applicable rules, and orderly, (2) responsibility is shown from the facts found by researchers that they must be ready and accept sanctions or punishments for actions they violate, (3) honesty, very instrumental in educating and accustoming students to always tell the truth,  They are required to always be mandated to school rules.